PANTAI PASIR PADI (PADDY SAND BEACH) OF BANGKA ISLAND; CRABS (Scopimera sp) POPULATION, FEEDING BEHAVIOUR AND THEIR BIRD PREDATOR - Marisa, Hanifa; Ridho, Mohammad Rasyid; Sarno, - (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
An observation about beach crab (Scopimera sp) population, their feeding behaviour and predator bird had been done at October 9 th, 2014 in Pantai Pasir Padi, Eastern Bangka Island beach, near Pangkal Pinang town. Ten 1 meter square plots were put at sandy beach and number of Scopimera sp be counted by the number of their hole nest home. Their feeding behaviour observed directly by eye-watching and video making. The threatening of bird predator was noted too. The investigation find out that the mean of crabs population is 17 individu/m2 . They come out from home hole for feeding around by sieving wet sand that be taken by front legs, obsorb organic nutrious material by mouth and kick residual sand to behind legs, move it as a small sand ball to right of left back side. Production of small ball sand were about 15 - 30 balls /per minute. For making the nest hole, bigger sand ball were produced about 7 – 9 ball/minute; ball colour is same with under layer beach sand; quite grey. The crabs run instinctivey fast, when the threat come from their natural enemy, predator bird, Actitis hypoleucos. Bird searching behaviour look adapted to the fast run of crab.